Clinical and Pain-Related Characteristics of Idiopathic First Bite Syndrome Induced by Taste in Japanese Patients without Diabetes: A Retrospective Study of Five Cases - Masatoshi Chiba; Hiroaki Hirotani; Tetsu Takahashi (Pain Research and Management)
Objective. First bite syndrome (FBS) is a condition in which the first bite of each meal causes parotid pain. Etiologies of FBS include prior surgery of the upper cervical region and, rarely, head and neck tumors. Idiopathic FBS rarely presents in patients without a history of surgery or evidence of an underlying tumor. Idiopathic FBS may be categorized into two subtypes: that in patients with diabetes and that in patients without diabetes. Idiopathic FBS in patients without diabetes may be overlooked or misdiagnosed because the condition has been described only in a few case reports. We aimed to identify the clinical and pain-related characteristics of idiopathic FBS in patients without diabetes. Methods. We retrospectively analyzed the clinical data of five patients without diabetes who were diagnosed with idiopathic FBS in our department between January 2010 and December 2016. Results. Four of the five patients were female, and the overall median age was 52 years (range: 13–61). All patients immediately experienced parotid pain upon tasting food without chewing. Addition of an acidic solution to the ipsilateral posterior third of the tongue evoked parotid pain. The median degree of pain intensity and interference with eating due to pain was 9 (range: 3–10) and 9 (range: 5–10) on a numerical rating scale of 0–10, respectively. Idiopathic FBS was bilateral in two patients. Two patients had tenderness on mild pressure over the affected parotid region. Two patients presented with ipsilateral idiopathic Horner’s syndrome. Conclusions. Our findings indicate that the characteristics of idiopathic FBS in patients without diabetes are largely consistent with those previously reported in postoperative FBS, supporting the notion that idiopathic FBS is a subtype of FBS. Thus, it is necessary to consider idiopathic FBS during the evaluation of facial pain triggered at the beginning of a meal.